Impact of COVID-19 on the education and healthcare services of persons with disabilities in Lebanon - Shuayb, Itab; Doueiry, Sabine (Frontiers in Public Health, 2023)
This study aimed to examine the impact of the compounding crises that engulfed Lebanon during the Covid-19 pandemic on the schooling and healthcare opportunities and experiences of people with disabilities. In addition, the study explored how the interaction of disability with other layers of discrimination (e.g., gender, and socioeconomic) further exacerbated the risk of exclusion from mainstream education and healthcare services. The study adopted qualitative research methods to unpack these complex issues. This included a desk review of 37 available research studies, reports, policies, procedures, notes, and rapid analysis reports conducted by governmental authorities such as the ministry of public health, international NGOs, and UN agencies. Moreover, the researcher reviewed and analyzed social media content and Covid-19 awareness campaigns to investigate to what extent the COVID-19 awareness campaigns and media information acknowledged people with disabilities (PWD) needs in their media content and to what extent such information was particularly accessible for people with sensory and cognitive disabilities and older generation. Furthermore, eighteen personal (virtual) open-ended interviews were conducted with service recipients who have disabilities, or with their parents, if they were below eighteen, local, and international disability organizations, and stakeholders from the educational and healthcare services. The outcome findings of interviews revealed that most people’s lives and daily activities were affected by Covid-19 lockdown restrictions, including PWD who faced barriers before the pandemic. Five main themes were identified at the policy and decision levels and the academic and healthcare services levels that hindered people with disabilities to gain access to education and healthcare. The five key findings, implications, and recommendations were presented and discussed.